2019
DOI: 10.1080/20008198.2019.1700621
|View full text |Cite
|
Sign up to set email alerts
|

Complex trauma, PTSD and complex PTSD in African refugees

Abstract: Background: The introduction of the diagnosis of complex posttraumatic stress disorder (CPTSD) by ICD-11 is a turning point in the field of traumatic stress studies. It's therefore important to examine the validity of CPTSD in refugee groups exposed to complex trauma (CT) defined as a repeated, prolonged, interpersonal traumatic event. Objective: The objective of this study was to compare DSM-5 and ICD-11 post-traumatic stress disorder diagnoses and to evaluate the discriminant validity of ICD-11 PTSD and CPTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 59 publications
(74 reference statements)
7
64
3
1
Order By: Relevance
“…Our findings contrast with research showing that differences between PTSD and CPTSD are related to symptom severity only, with CPTSD representing a more severe form of PTSD (Wolf et al, 2015). These findings are also consistent with those of several previous studies (Barbieri et al, 2019;Hyland et al, 2018;Karatzias et al, 2017;Kazlauskas et al, 2020;Murphy et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings contrast with research showing that differences between PTSD and CPTSD are related to symptom severity only, with CPTSD representing a more severe form of PTSD (Wolf et al, 2015). These findings are also consistent with those of several previous studies (Barbieri et al, 2019;Hyland et al, 2018;Karatzias et al, 2017;Kazlauskas et al, 2020;Murphy et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…Surprisingly, our data supported the emergence of another distinct class, namely a DSO class. Most previous studies have not found evidence of this class (Barbieri et al, 2019;Hyland et al, 2018;Jowett et al, 2019;Karatzias et al, 2017;Kazlauskas et al, 2018;Murphy et al, 2016). However, Kazlauskas et al (2020) also reported a DSO class in their study examining the validity of PTSD and CPTSD in adolescents, albeit with an adapted version of the ITQ best suited to their sample.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to the DSM-5 criteria the rate of probable PTSD (79.5%) was high in the current sample but consistent with findings of other previous studies investigating samples of treatment-seeking refugees resettled in Europe which reported DSM-IV PTSD rates of 82% (Teodorescu et al, 2012) and 94% (Teegen & Vogt, 2002). In a slightly different sample to the one of the current study, the reported DSM-5 PTSD rate was 79.0% (Barbieri et al, 2019). Meta-analytic findings have suggested that the prevalence of PTSD in refugee groups was approximately 30% (Steel et al, 2009).…”
Section: Discussioncontrasting
confidence: 64%
“…According to the World Health Organization (18), PTSD is defined by the core symptoms of intrusiveness or re-experiencing the trauma (nightmares, flashbacks, and recurring memories), hyperarousal (difficulty sleeping, irritability, and hypervigilance), and avoidance (reminders of events and dissociation) (17). Past research in asylum-seeking and refugee populations from Africa found PTSD rates of up to 79% (19)(20)(21). Individuals without secure residency status-be it pending cases (22,23), rejected asylum seekers (24,25), or undocumented migrants (26)-appear to be at a particularly high risk for ongoing mental health problems and post-migration stress (25,27).…”
Section: Introductionmentioning
confidence: 99%